FORMATION PROFESSIONALLY SIGNIFICANT QUALITIES OF FUTURE ENGINEERS IN THE PROCESS OF PROFESSIONAL TRAINING AT THE TECHNICAL UNIVERSITY - Кокарэва, А. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article the problem of formation of professionally significant qualities of future engineers in the professional training at the Technical University. We consider the interpretation of the concept of «professionally important qualities» of modern domestic and foreign researchers, given the author’s definition of this concept. The technology of formation of professionally significant qualities of future engineers, which includes factors are favorable for the formation of said technology